VALIDITAS LKPD IPAS BERBASIS PROBLEM BASED LEARNING KELAS IV SD NEGERI 41 PONTIANAK UTARA - Fakhruddin, Ahmad Rofi'ul; Kresnadi, Hery; Halidjah, Siti (Universitas Tanjungpura, 2025)
This study aims to describe the validity of student worksheets based on Problem Based Learning in grade IV science learning at SD Negeri 41 North Pontianak. This research is a type of research and development with reference to the ADDIE development model. The research method used is a mixed research method between quantitative research and qualitative research. The data source of this study is the results of validation from 2 material experts, 2 linguists, and 2 media experts. The data collection techniques used are interviews and questionnaires. The validity of student worksheets is carried out in 3 stages, namely Analyze, Design, and Development. The results of the study showed that the validity of the student worksheets based on the results of validation from material experts on the material aspect obtained a percentage of 93.35% including in the